Stability of agronomic traits in interspecific hybrid potato clones in the Central Region of European Russia - M. S. Khlopyuk; N. A. Chalaya; E. V. Rogozina (Труды по прикладной ботанике, генетике и селекции)
Background. Yield stability is a necessary trait for sustainable potato production under climate change. Potato breeding is based on crosses between parental lines selected for a set of important traits: productivity, structural yield components, and resistance to abiotic and biotic stresses. Data on plant responses to environmental conditions allows breeders to conduct informed selection of plant forms for crossing. The objective of this work was to characterize interspecific potato hybrids in terms of their productivity, yield plasticity and stability in the Central Region of European Russia.Materials and methods. For seven years (2014–2020), 19 hybrids and cv. ‘Favorit’ (reference) were assessed for productivity, number of tubers per plant, mean tuber weight, marketability, and resistance to late blight. Growing conditions were characterized using the hydrothermal coefficient. Environmental sustainability was determined by calculating the parameters of plasticity (bI) and stability (σ2) according to N. P. Sklyarova and V. A. Zharova.Results. Positive and negative anomalies in heat or moisture supply were observed during the test years. The maximum productivity was obtained in 2016, with heavy rainfall and higher temperatures; the minimum, in the hot and dry 2018. For productivity, the effect sizes of the factors “variety” and “year” were 29% and 38%, respectively. Hybrids with yield levels close to cv. ‘Favorit’ were identified: 117-2, 122-29, 99-6-5, 99-1-3, 99-6-6, and 34-5-2003. ‘Favorit’ is an intensive-type cultivar, with low yield stability. Hybrid 135-2-2006, also of the intensive type, had a stable yield, but developed medium-sized tubers and was less productive than other accessions. Hybrid 117-2 is of the extensive type, with medium stability, while hybrids 8-3-2004 and 135-5-2005 demonstrated high environmental plasticity and yield stability.